INTERNALISASI NILAI-NILAI EKOLOGI ISLAM MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI BOARDING SCHOOL DARUL MUHAJIRIN TRAILU - Heriady; Zainuddin; Ridwan; Amaluddin (Universitas Andi Djemma, 2026)
The increasingly complex environmental crisis demands an educational approach that is not only technical but also based on values ​​and ethics. Islam, as a comprehensive religion, has ecological teachings that position humans as caliphs on earth with the responsibility to maintain the balance and sustainability of nature. This study aims to analyze the process of internalizing Islamic ecological values ​​through Islamic Religious Education (PAI) learning at the Darul Muhajirin Trailu Boarding School. This study used a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with PAI teachers, boarding school administrators, and students, as well as documentation studies of the curriculum and institutional activities. Data analysis was conducted using thematic analysis with triangulation techniques to ensure data validity. The results show that the internalization of Islamic ecological values ​​occurs through cognitive, affective, and conative stages, which are integrated into PAI learning and reinforced by the boarding school culture. Islamic ecological values ​​such as trustworthiness (amanah), balance (mīzān), and the prohibition of causing harm (fasād) are instilled not only through learning materials but also through teacher role models and the daily lives of students. However, this study also found that the internalization of these values ​​is still implicit and not systematically structured within the Islamic Religious Education (PAI) curriculum. This study recommends strengthening the integration of Islamic ecological values ​​within the Islamic Religious Education (ISE) curriculum and developing experiential learning in boarding school environments.